SOCIAL AND ECONOMIC ESSENCE OF COMPULSORY INSURANCE (International Journal of Business, Law and Political Science, 2024)
Through the mandatory insurance system, the state participates in solving social problems of society's development. The importance and nature of compulsory insurance is revealed in the article.